Settlement of Bankruptcy Assets in A Form of Crypto Assets Throughout Bankcruptcy Process - Hidayatullah, Tomi; Subagyono, Bambang Sugeng Ariadi; Chumaida, Zahry Vandawati; Aditya, Kukuh Leksono Suminaring (Fakultas Hukum Universitas Airlangga, 2023)
AbstractThis research analyzes Crypto Assets as bankruptcy assets in the procedures for settlement by the curator in relation to statutory regulations, as well as the criteria for objects that can be included in bankruptcy assets. Generally, wealth is in the form of objects that can be seen, but the emergence of Crypto Assets in society breaks the stigma that exists in general. Based on bankruptcy practices in Indonesia, the categories or characteristics of objects that can be included as bankruptcy assets belonging to debtors are object that have resale value or economic value. This research is juridical-normative in nature. The results of this research show that crypto assets have met the classification as intangible objects. As bankruptcy assets, Crypto Assets cannot necessarily be used as a means of paying debts to creditors, because in Indonesia Crypto Assets are only allowed as an investment tool. However, Crypto Assets as bankruptcy assets must first be cleared by the curator until they are in the form of rupiah currency through certain stages in accordance with applicable law and regulations.Keywords: Bankruptcy; Bankruptcy Assets; Crypto Assets; Settlement.